Lipid-Protein Interactions Methods and Protocols - Kleinschmidt, Jörg H.; Kleinschmidt, Jörg H. (Methods in Molecular Biology, 2013)
Biological membranes are the essential structuring elements of all living cells. Many enzymatic reactions take place at the membrane-water interface. To gain detailed insight into membrane properties, it is therefore of great importance to understand the complex nature of the interactions of membrane proteins with lipids. Lipid-Protein Interactions: Methods and Protocols provides a selection of protocols to examine protein-lipid interactions, membrane and membrane protein structure, how membrane proteins affect lipids and how they are in turn affected by the lipid bilayer and lipid properties. The methods described here are all actively used, complementary, and necessary to obtain comprehensive information about membrane structure and function. They include label-free approaches, imaging techniques and spectroscopic methodologies. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Lipid-Protein Interactions: Methods and Protocols seeks to serve both professional and novices with its wide range of the methods frequently used in this area of research.